How do consumers infer corporate social responsibility? The role of organisation size. Issue 4 (4th March 2014) - Green, Todd; Peloza, John
ABSTRACT Consumers are generally supportive of firms that engage in corporate social responsibility (CSR) activities. However, consumers are also largely unaware of CSR activities of firms and often use available information to infer CSR. The current study utilises in‐depth consumer interviews to explore the influence of firm size on consumer perceptions of both CSR and corporate socially irresponsible behaviour through the lens of attribution theory. We identify two key emerging antecedents – consumer trust and expectations for CSR engagement – that are influenced by organisation size and ultimately distinguish the types of attributions consumers hold towards CSR and corporate socially irresponsible behaviour. Specifically, consumers have greater levels of trust and significantly lower expectations for CSR engagement for small firms. Conversely, a lack of trust exists amongst consumers towards large firms along with greater expectations for CSR engagement. Although the interview findings generally suggest that small firms benefit from CSR engagement because of positive attributions that consumers hold, we also identify opportunities for large firms to develop positive attributions amongst consumers. Further, we find that consumers are often willing to accept socially irresponsible behaviour by small firms whereas showing very little tolerance for similar transgressions by large firms. Copyright © 2014 John Wiley & Sons, Ltd.